O‘ZBEKISTON RESPUBLIKASIDA QISHLOQ XO‘JALIGI MAHSULOTLARINI YETISHTIRISH VA TASHISHNING HOZIRGI HOLATI - Ergashev, B.Z. (SCIENCE and SOCIETY, 2024)
The article analyzes the processes of transportation of fruits and vegetables grown in the Republic of Uzbekistan, the geography of exports of growing regions, and analyzes the literature describing what obstacles the processes of transporting fruits and vegetables are currently facing and what methods are used to solve these problems. When transporting fruits and vegetables, an analysis of the transportation technology is carried out and the necessary conclusions are drawn.